Patterns of motorization development and next-generation mobility systems. (March 2017) - Ohta, Katsutoshi
Abstract: This paper discusses the appropriateness of the "3-stage urban transport policy development cycle" hypothesis proposed by Professor Peter Jones and the importance of both local development context and motorization transport culture in transport policy. It then makes some observations on the future prospects for sustainable cities and transport through major technological innovations in connected and autonomous vehicles, that is, in "Auto Sapiens" as next generation vehicles.